Rethinking chest imaging in childhood pneumonia: Ultrasound as the new norm - Khan, Mahnoor; Azam, Abdullah; Shahrukh, Tabassum (Journal of the Pakistan Medical Association, 2026)
Dear Editor, Pneumonia is a leading cause of morbidity and mortality among children. Clinical diagnosis can be challenging due to its variable presentation in paediatric patients.(1) Traditionally, chest X-rays have been used as the primary imaging tool; however, with growing concerns over radiation exposure ultrasound is increasingly being considered as a safer alternative, offering comparable and potentially superiorefficacy in diagnosing childhood pneumonia.(1,2) A meta-analysis published in 2023 provided corroborating evidence. It pooled data from 26 studies and showed that Thoracic ultrasound had a pooled sensitivity and specificity of 0.95 and 0.94, respectively, for diagnosing paediatric pneumonia.(1) Another meta-analysis comparing thoracic ultrasound and chest X-rays found supporting evidence favouring lung ultrasound. It highlighted the significantly higher sensitivity of lung ultrasound for detecting childhood pneumonia (0.95 vs 0.92). (3) The paediatric population, when exposed to even low-dose ionizing radiation, are at an increased risk of developing cancers, which can prove deadly. This can be circumvented by using ultrasound, which does not involve ionizing radiation.(4) Furthermore, this allows the physician to perform multiple scans to assess the progression of the disease without the concern of increased exposure to ionizing radiation. Ultrasound is also more time-efficient than X-ray, enabling quicker image acquisition and interpretation.(5) This attribute is of paramount importance when imaging children in distress, who may be unable to remain still and could distort an X-ray image. Additionally, using an ultrasound can help a clinician make more timely interventions as it produces quicker imaging findings as compared to an X-ray.(5) However, it is important to acknowledge the limitations of lung ultrasound, including its operator-dependency and poor visualisation of the mediastinum. Therefore, chest X-ray remains a necessary tool in certain complex cases. In light of these findings, the authors advocate for revising the current protocols being followed when suspecting pneumonia in a child, promoting ultrasound as a first-line imaging tool where appropriate. The authors call upon hospitals to equip paediatric departments with ultrasound imaging devices and to arrange structured training and accreditation programmes.